2001
DOI: 10.1046/j.1365-2796.2001.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin‐converting enzyme (ACE) gene polymorphisms and familial occurrence of sarcoidosis

Abstract: Objectives. The aim of this study was to test for genetic linkage and association between polymorphisms of the angiotensin-converting enzyme (ACE) gene and familial occurrence of sarcoidosis. Design, setting and subjects. German families with more than one member suffering from sarcoidosis were contacted and a DNA bank was established. Sixty-two families (140 patients, 77 females and 63 males, and 104 unaffected relatives) were genotyped for the ACE gene insertion/deletion (I/D) polymorphism and for two flanki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 23 publications
1
22
0
2
Order By: Relevance
“…ID), patients with the II genotype had 5.5 times higher disease risk (Tahir et al 2007). Schurmann et al studied German families and reported that the DD genotype was present at a high level in patients with sarcoidosis (Schurmann et al 2001). Similarly, Salobir et al observed that the D allele frequency was higher in a Slovenian patient group compared to the control group, and they suggested that I/D polymorphism in the ACE gene might be associated with predisposition to sarcoidosis (Salobir et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ID), patients with the II genotype had 5.5 times higher disease risk (Tahir et al 2007). Schurmann et al studied German families and reported that the DD genotype was present at a high level in patients with sarcoidosis (Schurmann et al 2001). Similarly, Salobir et al observed that the D allele frequency was higher in a Slovenian patient group compared to the control group, and they suggested that I/D polymorphism in the ACE gene might be associated with predisposition to sarcoidosis (Salobir et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Along with the detection of familial sarcoidosis, research on genetic predisposition to sarcoidosis has gained momentum (Fite et al 1998;Rybicki et al 1996;Sverrild et al 2008). However, contradictory results were obtained using different ethnic groups; therefore, further studies are required to test whether the ACE genotype is linked to sarcoidosis predisposition (Maliarik et al 1998;McGrath et al 2001;Alia et al 2005;Kruit et al 2010;Schurmann et al 2001;Hatemi et al 2001). The objectives of our study were to determine the distribution of I/D polymorphism in the ACE gene in Turkish patients as a distinct ethnic group and to investigate whether such polymorphism is associated with a predisposition to sarcoidosis.…”
Section: Introductionmentioning
confidence: 99%
“…Conflicting case-control study results with respect to sarcoidosis risk exist for polymorphisms in the ACE [7][8][9][10][11][12][36][37][38][39][40], VDR [27,41], and TNF-a [17][18][19][20]42] genes (table 5). Therefore, the current authors tested polymorphisms in these genes for associations with sarcoidosis in African-American families.…”
Section: Discussionmentioning
confidence: 99%
“…Association studies of the ACE I/D polymorphism and sarcoidosis have produced mixed results. The ACE D allele, which is associated with higher serum ACE levels [6], has been found associated with increased sarcoidosis risk in African Americans [8], Japanese women [7] and in sarcoid-affected family members from a German population [9]. Conversely, other studies in both Caucasians [10,11] and Japanese [12] have failed to find an association between the ACE I/D polymorphism and sarcoidosis susceptibility or progression.…”
mentioning
confidence: 99%
“…Thirtysix articles were excluded after screening the titles and abstracts because they were either review articles, editorials, or irrelevant to the current study. Of the remaining 25 full-text articles (Arbustini et al, 1996;Furuya et al, 1996;Császár et al, 1997;Sharma et al, 1997;Tomita et al, 1997;Xu et al, 1997;Garrib et al, 1998;Maliarik et al, 1998;Niimi et al, 1998;Takemoto et al, 1998;Pietinalho et al, 1999;Stokes et al, 1999;Papadopoulos et al, 2000;McGrath et al, 2001;Ruprecht et al, 2001;Schürmann et al, 2001;Planck et al, 2002;Alía et al, 2005;Biller et al, 2006;Kruit et al, 2007;Salobir et al, 2007;Tahir et al, 2007;Biller et al, 2009;Kruit et al, 2010;Yilmaz et al, 2012), 2 lacked controls (Stokes et al, 1999;Schürmann et al, 2001), and 2 did not examine patients with sarcoidosis (Ruprecht et al, 2001;Biller et al, 2006); these 4 articles were thus excluded. An additional 3 articles (Császár et al, 1997;Niimi et al, 1998;Kruit et al, 2007) were also excluded because of incomplete reporting of data.…”
Section: Literature Searchmentioning
confidence: 99%